Fabrication Of 3D Biodegradable PBAT/PLA Blends Electrospun Nanofiber For Cardiac Patch Application - Azman, Syamil Akhyar (Universiti Sains Malaysia, 2022)
Usually both polybutylene adipate terephthalate (PBAT) and polylactic acid (PLA) have been compounded with other biodegradable synthetic polymers, namely polycaprolactone (PCL), polyglycolic acid (PGA), polyglycerol sebacate (PGS) and several other natural biodegradable polymers such as gelatin, chitosan and collagen. However, there are few studies in the literature on PBAT and PLA binary blends for cardiac tissue engineering. Thus, in this work, blends between these polymers were analyzed to investigate the influence of the pure PBAT and pure PLA blend and its ratio on electrospun fibre scaffolds' physical, mechanical, and thermal characteristics. It was found that 12.5wt % solution concentration is the optimum electrospinning parameter for the fabrication of PBAT/PLA blend. PBAT/PLA blend with ratio of 60/40 produced the most feasible enhancement in properties even though the obtained results were comparatively low than pure PBAT and pure PLA. Fourier Transform Infrared (FTIR) analysis depicts that PBAT/PLA spectrum was quite similar to pure PBAT IR spectra. When a higher portion of PLA was added to the blending; Scanning Electron Microscopy (SEM) analysis indicates smooth and aligned fibre morphology, water contact angle measurement illustrates a reduction in the hydrophobicity, mechanical properties (rigidity and toughness) and thermal stability of PBAT/PLA blend was enhanced.